Efeitos antiinflamatÃrios e antinociceptivos do fitol, um ativador de NADPH oxidase, e tadalafil, um inibidor de 5-fosfodiesterase, em modelos experimentais - Ana Caroline Rocha de Melo Leite (2010)
Reactive oxygen species (ROS) and nitrogen (RNS) promote tissue destruction in inflammatory diseases such as rheumatoid arthritis. However, agents that activate ROS production by NADPH oxidase reduce inflammation in experimental models. Considering the controversial participation of via NO-cGMP in nociception, inhibitors of phosphodiesterase-5 have controversial role in models of pain. In this study, it was investigated the effect of phytol, an activating of NADPH oxidase, and tadalafil, a phosphodiesterase-5 inhibitor, in models of zymosan-induced arthritis (ZyA) and Zy-induced peritonitis as well as osteoarthritis by anterior cruciate ligament transection (ACLT) and acetic acid writhing. In ZyA, rats and mice received 1 mg and 100 Âg zymosan intra-articular (i.art.), respectively. In peritonitis or writhing, mice received 100 Âg of Zy or acetic acid intraperitoneal (i.p.), respectively. In osteoarthritis, rats underwent ACLT. Rats received phytol subcutaneous (s.c) 30 min â 8 d before ZyA or tadalafil orally (p.o.) 2 h after Zy. Other rats received SIN-1 (i.art.), ODQ (i.art.) or naloxone (i.p.) 1.5 â 2 h after Zy. Mice received phytol s.c. 1 â 24 h before Zy i.art.. Other mice received phytol i.art. 1 h before or 1.5 h after Zy. In peritonitis or writhing, phytol s.c. was injected 30 min â 24 h before Zy or acetic acid, respectively. In osteoarthritis, it was done one s.c. phytol administration 5 d before and 35 d after ACLT or tadalafil p.o. from 4 â 7 d after ACLT. Control groups received Zy i.art. or i.p. or acetic acid or were submitted to ACLT. The hypernociception was assessed by articular incapacitation test recorded as paw elevation time - PET. Cell influx (CI) was quantified in joint lavage after 6 h or 7 d of ZyA and in peritoneal lavage after 4 h of peritonitis. NO, IL-1, TNF-α, IL-10 and CINC-1 were measured in acute articular supernatant in rats while cartilage glycosaminoglycans (GAGs) were quantified after 7 d of ZyA in rats. Results were expressed as mean Â SEM, submitted to ANOVA and Tukey test or to Studentâs t test (P <0.05). In writhing, data were expressed as median and submitted to the Kruskal-Wallis test (P<0.05). In ZyA, systemic (s.c.) and prophylactic administration of phytol decreased acute CI, independent of dose and time of administration, in mice. Local (i.art.) prophylactic or therapy injection of phytol decreased significantly CI in mice submitted to ZyA. Similar to the acute phase, phytol reduced significantly chronic CI. In ZyA in rats, phytol decreased acute and chronic CI as well as PET. As to GAGs, there was significant increase by phytol, reaching a level similar to naive animals. In peritonitis or writhing, phytol decreased CI or number of writhing, respectively, regardless of administration time. In osteoarthritis, phytol decreased significantly PET on days 1, 7, 9 and 11 as well as the peak between 4th and 7th d after ACLT. NO, IL-1, TNF-α and IL-10 were reduced in ZyA too. As tadalafil, there was decreased acute IC and PET, in a dose-dependent, in ZyA in rats. ODQ, administered prior tadalafil, reversed tadalafil effect about CI and PET in ZyA, that didnât happen with a prior injection of naloxone. Tadalafil reduced TNF-α and IL-10 in ZyA and PET in osteoarthritis. The results show that phytol promotes anti-inflammatory and antinociceptive effects species, stimulus, tissue and route of administration independent. These actions are associate with the local release of NO and cytokines. In parallel, tadalafil has similar anti-inflammatory and antinociceptive effects associated with the lock on the local release of TNF. These findings suggest that activators of NADPH oxidase, possibly from compounds in the diet, modify the natural history of inflammatory arthropathy. The antinociceptive effect of phosphodiesterase-5 inhibitors should be explored, since these compounds are progressive indication in inflammatory diseases that occur with vascular damage and hypoxia.